A real-life observational study of the effectiveness of FACT in a Dutch mental health region - Poddighe Giovanni; de Bie Arthur; à Campo Joost; Driessen Ger; Bak Maarten; Maarschalkerweerd Myrte; Drukker Marjan; van Os Jim; Delespaul Philippe (BMC Psychiatry, 2008)
Abstract Background ACT is an effective community treatment but causes discontinuity of care between acutely ill and currently stable patient groups. The Dutch variant of ACT, FACT, combines both intensive ACT treatment and care for patients requiring less intensive care at one time point yet likely to need ACT in the future. It may be hypothesised that this case mix is not beneficial for patients requiring intensive care, as other patient groups may "dilute" care provision. The effectiveness of FACT was compared with standard care, with a particular focus on possible moderating effects of patient characteristics within the case mix in FACT. Methods In 2002, three FACT teams were implemented in a Dutch region in which a cumulative routine outcome measurement system was in place. Patients receiving FACT were compared with patients receiving standard treatment, matched on "baseline" symptom severity and age, using propensity score matching. Outcome was the probability of being in symptomatic remission of psychotic symptoms. Results The probability of symptomatic remission was higher for SMI patients receiving FACT than for controls receiving standard treatment, but only when there was an unmet need for care with respect to psychotic symptoms (OR = 6.70, p = 0.002; 95% CI = 1.97 – 22.7). Conclusion Compared to standard care, FACT was more rather than less effective, but only when a need for care with respect to psychotic symptoms is present. This suggests that there is no adverse effect of using broader patient mixes in providing continuity of care for all patients with severe mental illness in a defined geographical area.